Analysis of the influence of online menus on consumer purchase intention with contamination concern during the Covid-19 pandemic - Pipit Agustiyanti Mulyadi; Ignatius Heruwasto (President University, 2022)
The Covid-19 pandemic is causing global concern, not only in Indonesia but also throughout the world. This is due to the coronavirus, which spreads quickly, especially at the end of 2019, and causes relatively high contamination. The perceived impact also highlights the phenomenon of changes in consumer behavior. To overcome the impact of Covid-19 itself, the marketer is trying to make breakthroughs with online menus that offer their business products but adhere to the health protocol by minimizing the risk of Covid-19, the effects of contamination, and hygiene on the touch of the products offered to attract consumer buying interest. The purpose of this study is to analyze the effect of the online menu used in businesses circumstances in restaurants by analyzing the influence of the stimulus Covid-19 Risk, Hygiene through Perceived Contamination, Ease of App Use through Perceived Convenience, and Menu Visual Appeal and Informativeness that effect Desire for Food to the consumer's Purchase Intention. This research was conducted in Indonesia's food and beverage industry using the Stimulus Organism Response model through quantitative research methods with confirmatory research. Data collection techniques by electronic survey with convenience sampling technique as many as 357 respondents shop for food using the online menu at restaurants, especially during the pandemic. Based on the results of the study, it can be concluded that Perception of Covid-19 Risk, Hygiene, Perceived Contamination, Perceived Convenience, and Desire for Food are considered by consumers in their buying interest in food (purchase intention).